Role of Climate Change in Afghanistan’s Geopolitical Power - Yar, Fayaz Gul Mazloum (Universitas Negeri Semarang, 2024)
The most significant environmental threats today are global warming and climate change. The effects of climate change include water and food scarcity, disease, unemployment, migration, poverty, resource conflicts, and global instability. This study examines the role of climate change in Afghanistan’s geopolitical power. This study employs a descriptive-analytical approach and a survey method. The statistical research community includes experts and specialists in geopolitics, political science, climate science, and university professors. The questionnaire was distributed among them based on indicators related to climate change, development, and geopolitics. 80 questionnaires were collected. On the basis of these findings, a significant and inverse relationship exists between the impacts of climate change and development. Furthermore, the reduction in the development process has a significant and negative impact on Afghanistan’s geopolitical power. Finally, the reduction in development affects the change. Climate plays a mediating role in geopolitics. Then, the priority of parameters influencing climate change in geopolitics was discussed using Friedman’s comparison test. These parameters include 1) poverty and social anomalies, drought, and migration. In the suggestions section, it is emphasized that there is a need to implement effective methods, such as irrigation and the use of clean energy, to reduce greenhouse gas emissions and adapt to the impacts of climate change.